Vitamin D Deficiency Among Professional Basketball Players. Issue 7 (6th July 2016) - Fishman, Matthew P.; Lombardo, Stephen J.; Kharrazi, F. Daniel
Background: Vitamin D plays an important role in several systems of the human body. Various studies have linked vitamin D deficiency to stress and insufficiency fractures, muscle recovery and function, and athletic performance. The prevalence of vitamin D deficiency in the elite athletic population has not been extensively studied, and very few reports exist among professional athletes. Hypothesis: There is a high prevalence of vitamin D deficiency or insufficiency among players attending the National Basketball Association (NBA) Combine. Study Design: Cross-sectional study; Level of evidence, 3. Methods: This is a retrospective review of data previously collected as part of the routine medical evaluation of players in the NBA Combines from 2009 through 2013. Player parameters evaluated were height, weight, body mass index (BMI), and vitamin D level. Statistical analysis using t tests and analysis of variance was used to detect any correlation between the player parameters and vitamin D level. Vitamin D levels were categorized as deficient (<20 ng/mL), insufficient (20-32 ng/mL), and sufficient (>32 ng/mL). Results: After institutional review board approval was submitted to the NBA, the NBA released deidentified data on 279 players who participated in the combines from 2009 through 2013. There were 90 players (32.3%) who were deficient, 131 players (47.0%) who were insufficient, and 58 players (20.8%) who were sufficient. A total of 221 players (79.3%) were either vitamin D deficient or insufficient. Among all players included, the average vitamin D level was 25.6 ± 10.2 ng/mL. Among the players who were deficient, insufficient, and sufficient, the average vitamin D levels were 16.1 ± 2.1 ng/mL, 25.0 ± 3.4 ng/mL, and 41.6 ± 8.6 ng/mL, respectively. Player height and weight were significantly increased in vitamin D–sufficient players compared with players who were not sufficient ( P = .0008 and .009, respectively). Player age and BMI did not significantly differ depending on vitamin D status ( P = .15 and .77, respectively). Conclusion: There is a high prevalence of vitamin D deficiency or insufficiency among participants in the NBA Combines. As a result, there should be a high suspicion for this metabolic abnormality among elite basketball players. Clinical Relevance: Vitamin D level has been linked to bone health, muscle recovery and function, and athletic performance. Because of the high prevalence of vitamin D deficiency in the NBA Combines, clinicians should maintain a high suspicion for vitamin D abnormalities among elite basketball players.